2016
DOI: 10.1016/j.matdes.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of α-Fe2O3 micro-ellipsoids by surfactant-free hydrothermal method for sub-ppm level H2S detection

Abstract: The α-Fe 2 O 3 micro-ellipsoids were prepared using a facile hydrothermal process without any surfactant or template, and their morphological, structural and H 2 S sensing properties were investigated.The α-Fe 2 O 3 showed uniform micro-ellipsoids with a long axis diameter of 1.7 µm and a short axis diameter of 1.2 µm. Detailed structural analysis confirmed that the synthesized α-Fe 2 O 3 micro-ellipsoids were compact particles with a hexagonal structure. Gas sensor base on the α-Fe 2 O 3 micro-ellipsoids show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Sensors made of metal oxide nanostructures are normally effective to detect both UV light and poisonous gases, and developing new types of nanostructured sensing materials is one of the key factors for the successful application of these sensors. Many types of nanostructured metal oxides have been investigated to detect UV light or poisonous gases, and these include SnO2 [3], ZnO [4,5], Fe2O3 [6], TiO2 [7], NiO [8], In2O3 [9], CuO [10], and so on. Among these, In2O3 nanostructures have been proven to have good responses to UV light and various toxic gases.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors made of metal oxide nanostructures are normally effective to detect both UV light and poisonous gases, and developing new types of nanostructured sensing materials is one of the key factors for the successful application of these sensors. Many types of nanostructured metal oxides have been investigated to detect UV light or poisonous gases, and these include SnO2 [3], ZnO [4,5], Fe2O3 [6], TiO2 [7], NiO [8], In2O3 [9], CuO [10], and so on. Among these, In2O3 nanostructures have been proven to have good responses to UV light and various toxic gases.…”
Section: Introductionmentioning
confidence: 99%
“…The response and recovery behaviors of CeO2 and Ce0.94Zr0.06O2 nano-sheets based gas sensors were investigated at room temperature. The gas response(R) of sensors is defined as the resistance ratio: R= Ra/Rg [37], (Rg: resistance of sensors in the target gas; Ra: resistance of sensors in air).…”
Section: Gas Sensing Properties Of Ceo2 and Ce094zr006o2 Nano-sheetmentioning
confidence: 99%
“…16 Among them, the α-Fe2O3 nanomaterials are nontoxic, chemically stable and low cost, which are good sensing materials to detect ethanol, 17 acetone, 18 trimethylamine, 19 NH3 20 and H2S. 21 It was reported that α-Fe2O3 nanomaterials exhibit good sensing performance for H2S. 16 It is well known that the size, morphology and porosity of α-Fe2O3 nanomaterials significantly affect their gas sensing properties, such as sensitivity, response/recovery times (tres/trec), selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is well known that the size, morphology and porosity of α-Fe2O3 nanomaterials significantly affect their gas sensing properties, such as sensitivity, response/recovery times (tres/trec), selectivity and stability. Therefore, great effort has been made to prepare different α-Fe2O3 nanostructures to improve the H2S gas sensing performance, such as flute-like porous nanorods, 22 micro-ellipsoids, 21 sheaf-like architectures, 17 hollow urchin-like spheres 23 and microcubes 24 , etc. The sensing properties of H2S gas sensors based on different Fe2O3 nanostructures reported in literature are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%